The responsibility of the engineer and the market mechanism (Diametros, 2008)
The perspective of the ethics of responsibility can be regarded as a necessary and valuable complement to the traditional codes of engineering ethics. Adopting this perspective, I examine the impact of the market competition on the actions of engineers. I argue that both the absence of market competition (during the period of real socialism) and regarding it as a new absolute (as happens today) can lead to irresponsible behavior in the world of technology. I also attempt to show some normative elements in an engineer’s attitude that can prevent the latter phenomena.